Differentiation, technology, creativity, and equity in gifted mathematics education: A systematic review - Zahara Yuyun Nailufar; Budi Usodo; Riyadi Riyadi; Farida Nurhasanah (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2026)
Gifted students in mathematics possess advanced cognitive abilities that often require instructional approaches beyond conventional classroom practices. However, existing mathematics education practices frequently fall short in addressing both the intellectual and affective needs of this population. This study aims to systematically map and synthesize mathematics learning strategies for gifted students reported in the literature over the past decade. Employing a Systematic Literature Review (SLR) guided by the PRISMA protocol, this study analyzed 17 empirical articles published between 2015 and 2025 in Scopus-indexed journals. The analysis combined thematic synthesis and bibliometric techniques to identify dominant instructional approaches, emerging trends, and research patterns. The findings reveal that technology-enhanced learning and differentiated instruction are the most frequently adopted strategies, followed by creativity-oriented instruction, enrichment, self-regulated learning, and acceleration. In addition, recent studies increasingly emphasize equity-sensitive and culturally responsive approaches, particularly in addressing the needs of twice-exceptional students and those from diverse socioeconomic backgrounds. These results highlight the multidimensional nature of mathematical giftedness and underscore the importance of flexible, inclusive, and evidence-based instructional designs. This review provides a conceptual foundation for curriculum development, educational policy, and teacher professional development aimed at optimizing meaningful mathematics learning for gifted students across diverse educational contexts.